PROGRESS IN ESR DATING OF PLEISTOCENE CORALS - A NEW APPROACH FOR DE DETERMINATION - Schellmann G.; Radtke U. (My University, 2001)
ESR dating has been widely applied for dating of corals of the age up to 500,000 to 600,000 years ago. Many studies have yielded promising results but the accurate determination of the equivalent dose (DE) remains a major limitation. Inflexion points in the dose-response curve are shown to hinder correct fitting and limit the reliability of DE values. Here, we present a new approach to obtain more reliable DE values.
Keywords: Pleistocene; ESR dating; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен